Pengaruh Circuit Training terhadap Peningkatan Agility pada Pemain Futsal - Yeni, Yeni Tri Nurhayati; Wardana, Farid Aditya; Pawana, I Putu Alit (Penerbit Goodwood, 2024)
Purpose: Futsal requires skills and individual techniques such as agility and speed. Agility is the ability to change body position quickly without losing balance. Circuit training is a training system that can simultaneously improve the overall body fitness, the elements such as speed, agility, and other components of physical conditions. This study aims to determine the effect of circuit training on improving agility in futsal players. Methodology/approach: A quasi-experimental study was conducted among 26 male futsal players who were divided non-randomly into 2 groups of 13 people, 1) experimental group which was doing circuit training twice a week for 6 weeks; 2) control group. Agility was measured using the illinois agility test of both groups. Descriptive analysis was done by using EZR (Easy R) to find out the results of the study. Results/findings: The result of this study is the average difference between pretest-posttest circuit training groups was 0,95±0,23 and the control group 0,03±0,06. Analysis of different effect between both groups means by using two sample t-test showed a result of p = 0,001 where the value of p value <0.05 so that H1 is accepted which means that there are significant differences in the effect on the research subject after being given circuit training. In conclusion, there was significant effect of circuit training to improve agility in futsal players. This results show that circuit training was reasonably effective in improving agility, suggesting that other factors such as BMI and training frequency should also be considered in future research. Based on the results of data analysis, it can be concluded that the provision of circuit training has an effect on increasing agility in futsal players as measured by the Illinois agility test measuring instrument at pre-test and post-test. Limitations: This study has several limitations. First, the sample size was relatively small, which may limit the generalizability of the findings. Second, there were potential external factors that were not strictly controlled, may still contributing to the study outcomes. Third, the study design was non-randomized, which could introduce selection bias. Contribution: This research is expected to increase knowledge, provide an alternative form of circuit training to increase the agility performance of futsal players